Analysis of Financial Ratios on Stock Prices with Profitability as a Moderating Variable for LQ45 Index Companies Listed on the Indonesia Stock Exchange - Shintianingrum, Oktavia; Takarini, Nurjanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this study is to examine the influence of financial ratios on stock prices, with a particular focus on the role of profitability as a moderating factor among LQ45 index companies listed on the Indonesia Stock Exchange between 2020 and 2023. The independent variables employed in this study are liquidity ratio (CR), solvency ratio (DER) and market value ratio (PER), in addition to profitability (EPS) as a moderating variable. The dependent variable is stock price. This study employs a sample of 23 selected companies included in the LQ45 index. The data analysis method utilised is multiple linear regression. The findings indicate that the liquidity ratio and solvency ratio exert no significant influence on the company's stock price. Conversely, the market value ratio exerts a significant effect on stock prices. Furthermore, profitability does not serve as a moderating variable for the liquidity and solvency ratios, whereas it does for the market value ratios on stock prices.